THROMBOLYTIC EFFECTS OF A POLYANIONIC COMPOUND (PENTOSAN POLYSULPHATE SP54 ) IN GERIATRIC PATIENTS - Vogel, G; Machulik, M (Thrombosis and Haemostasis, 1987)
In geriatric patients the use ofstreptokinase or urokinase is oftenlimited by contraindications, particularly hypertension. As it has been demonstrated by different authors, the polyanionic compound pentosanpolysulphate SP 54 induced an activation of both intrinsic and extrinsic pathway of fibrinolysis and produced a mild decrease of blood prssure. From thise characteristics pentosan polysulphate SP54 should be anideal thrombolytic agent in geriatric patients. To clarify this, an open prospective studie was performed. 24 patient(16 females, 8 males ) age 65 -78 years , suffering from thromboembolicprocesses ( 8 deep vein thrombosis(DVT), 16 thrombosis of reti na vessels ( TRV) were included. Pentosan polysulphat SP 54 (BENE-PHARMA Munchen, F.R.G.) was administred byintravenous infusion 300 mg daily over a period of 10 days. Venographyor ophthalmoskopie were repeated atday 11.Results:Side effects: Bleeding 0 ; thrombocytopenia 2It is concluded from these results, that pentosan polysulphate SP54is an useful thrombolytic agent in particular in geriatric patients suffering from hypertension.